Single-Visit Root Canal Treatment on a Mandibular First Premolar with Three Root Canals - Achmad Junaidi; Annisa Fitria Sari (Jurnal Sehat Indonesia (JUSINDO), 2026)
Background: In root canal treatment, accurate diagnosis of root canal morphology is crucial for treatment success. Vertucci reported that in mandibular premolars, 74% have one canal, 25.5% have two canals, and 0.5% have three canals. Therefore, pre-treatment radiography, careful examination, and appropriate techniques are essential to identify root canal orifices, especially in cases with canal variations. The purpose of this case report is to demonstrate the importance of knowledge about the morphology of the root canal system and how to manage root canal care in the first premolar tooth of the lower jaw with three root canals. Case: A 57-year-old female patient with a complaint of a large cavity of the left lower jaw premolar tooth, no pain and wants to be treated. The radiographic results showed that the tooth pulp was open and the morphology of the root canal showed that there were three root canals. Management: Access opening and search of three root canals is carried out using ultrasonic tips and magnification assistance with a dental microscope. The root canal is prepared with rotary NiTi fileby irrigation using 5.25% sodium hypochlorite, 17% EDTA. Obturation using thermal fill and the use of dental crowns as final restoration will be done at the next visit. Conclusion: An understanding of the morphology of the root canal system and the proper use of tools and materials will influence success in the treatment of complex root canals in premolar teeth with three root canals.